Power saving in distillation using complexes with coupled flows - A. V. Timoshenko; E. A. Anokhina; D. G. Rudakov; V. S. Timofeev; G. I. Tatsievskaya; Yu. V. Matyushenkova (Тонкие химические технологии, 2011)
The current state of distillation technologies based on the use of complexes with fully and partially bound threads is described. Data on the energy efficiency of complexes are presented.